PERBANDINGAN STATUS GIZI BAYI YANG MENDAPATKAN ASI EKSKLUSIF DAN ASI PARSIAL: SYSTEMATIC REVIEW - Andini, Gita; Pratiwi, Agnis Ika; Anisa, Fitri; Zanuba, Elsya Aghna; Herbawani, Chahya Kharin (J-KESMAS: Jurnal Kesehatan Masyarakat, 2024)
Coverage of exclusive breastfeeding in 2020 was only 43.8% globally. Giving breast milk exclusively to babies 0-6 months has been recommended by the World Health Organization (WHO) to support optimal growth of babies. This study aims to determine the benefits of exclusive breastfeeding on the nutritional status of babies and compare it with babies who receive partial breast milk. The method applied in this research is a systematic literature review of quantitative articles in Indonesian or English published in 2019-2024 using three databases: PubMed, ScienceDirect, and Google Scholar according to keywords. The study results showed that babies who received exclusive breast milk had more normal weight and height growth than those who received partial breast milk. Exclusive breastfeeding significantly benefits babies' nutritional status because the nutrients from breast milk that babies need for six months are distributed well. This research supports the WHO recommendation to provide exclusive breast milk for the first six months to ensure optimal baby growth